Vulnerability and welfare during multiple crises - van Asselt, Joanna; Lambrecht, Isabel B.; Aung, Zin Wai (International Food Policy Research Institute, 2024)
The triple transition that took place between 2011 and 2019 in Myanmar—from a planned to an open market economy, from military to civilian rule, from conflict to peace—was not without its limitations. As discussed in Chapter 1, poverty reduction was modest relative to economic growth, a fully democratic system was not established, and ethnic conflict continued in many areas. In this mixed context of social welfare improvements and unfulfilled reforms, COVID-19 hit—the first in a series of crises. The pandemic had an immediate adverse impact on Myanmar’s economy and pushed many households into poverty. Then, while the country remained under threat from the pandemic, in February 2021, the military took over in a coup, and Myanmar fell into a political crisis. Declines in welfare accelerated for many. One year later, the Myanmar economy faced sharp rises in prices for food, fuel, and fertilizer as a result of a global economic crisis triggered by the start of the conflict in Ukraine. This triple crisis—pandemic, political, economic— has had enormous impacts on welfare and livelihoods in Myanmar. (Chapter 1 summarizes how the triple crisis unfolded; refer to that chapter for details on the causes, levels, and apparent consequences of the sequence of shocks.)